Implementasi Sistem Pemerintahan Berbasis Elektronik (SPBE) di Dinas Komunikasi dan Informatika Kabupaten Sijunjung - Febrian Arga Wahyudi; Nora Eka Putri (Jurnal Administrasi Pemerintahan Desa, 2025)
Abstract: This research reveals how the Electronic-Based Government System is implemented in the Sijunjung Regency Communication and Information Service. In accordance with Sijunjung Regent Regulation Number 29 of 2019, the Sijunjung Regency Communication and Information Service was appointed as the agency responsible for the application of information and communication technology in the implementation of SPBE in Sijunjung Regency. Based on the results of monitoring and evaluation carried out by the Ministry of State Apparatus Empowerment, Reform and Bureaucracy (Kemen PAN RB) in 2022, Sijunjung Regency achieved the lowest SPBE index number 2 in West Sumatra Province with an index value of 2.18% (fair). Researchers used a quasi-qualitative research method (Quasi Qualitative) with a simple research design (SRD) approach. The informants in this research consisted of 9 people consisting of the regional secretary, three employees of the Communication and Information Department and 5 employees from each OPD who the author chose for research using purposive sampling. The data collection techniques applied in this research are observation, interviews and documentation. Meanwhile, the data analysis applied in this research uses triangulation techniques. Based on the results of the analysis using e-Government implementation theory according to Indrajit, the results obtained were that in application development not all OPDs coordinated with the Communication and Information Department in developing applications. Then training and competency development has been carried out by the Sijunjung district communications and information services office for all operators in agencies implementing SPBE. Regarding the availability of network infrastructure, there are still many network flashing spots in Sijunjung Regency. Regional regulations related to SPBE management have been prepared by the regional government of Sijunjung Regency. Human resource procurement is focused on adding employees who understand programming, and the capital used in implementing SPBE uses APBD with a limited budget.